1985
DOI: 10.1523/jneurosci.05-07-01755.1985
|View full text |Cite
|
Sign up to set email alerts
|

Slow axonal transport in acrylamide neuropathy: different abnormalities produced by single-dose and continuous administration

Abstract: Alterations in axonal caliber and neurofilament content have been associated with altered neurofilament transport in several models of neurofibrillary degeneration. Acrylamide intoxication provides a prototype of distal axonal degeneration, the most frequent pattern of axonal pathology in human and experimental neurotoxic injury. Neurofibrillary changes are a variable and often minor aspect of the early pathological changes observed in acrylamide intoxication, and previous studies of slow axonal transport have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 26 publications
(4 reference statements)
4
43
0
Order By: Relevance
“…Acrylamide-induced peripheral neuropathy is a well-established, reproducible rodent model of distal axonal degeneration (21). Acrylamide is known to interfere with slow axonal transport (22). Oral administration of acrylamide to rodents causes distal degeneration of motor axons, resulting in distal limb weakness (14,23).…”
Section: Resultsmentioning
confidence: 99%
“…Acrylamide-induced peripheral neuropathy is a well-established, reproducible rodent model of distal axonal degeneration (21). Acrylamide is known to interfere with slow axonal transport (22). Oral administration of acrylamide to rodents causes distal degeneration of motor axons, resulting in distal limb weakness (14,23).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to defects in vesicular transport, perturbations in axonal transport have been hypothesized to play a role in the pathogenesis of human diseases, including ALS (Price et al, 1975;Griffin and Price, 1976), and have been shown to occur in various animal models (Price et al, 1975;Griffin and Price, 1976;Griffin et al, 1978;Gold et al, 1985;Collard et al, 1995;Williamson and Cleveland, 1999). In studies of mutant SOD1 (Cu/Zn superoxide dismutase) mice, disruption of transport has been shown to antedate the onset of clinical signs (Williamson and Cleveland, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The neurotoxic action of AA was suggested to be due to effects on cells of the central and peripheral nervous system including changes in cellular metabolism (Howland et al, 1980;Brimijoin and Hammond,1985;Medrano and LoPachin, 1989;Exon, 2006), changes in gene transcription and protein synthesis (Cavanagh and Nolan, 1982a,b;Cavanagh, 1982;Cavanagh and Gysbers, 1983;Bisby and Redshaw, 1987;Lin et al, 2000;El-Alfy et al, 2011;Seale et al, 2012), effects on neurotransmitter levels and turn-over (Dixit et al, 1981;Uphouse and Russell, 1981;Aldous et al, 1983;Shi et al, 2012), binding to cellular proteins including damage to microtubular and neurofilamental proteins (Hashimoto and Aldridge, 1970;Tanii and Hashimoto, 1983;Carrington et al, 1991;Reagan et al, 1994;Abou-Donia, 1996, 1997;Lapadula et al, 1989;Xiwen et al, 1992), changes in ion distribution (Lehning et al, 1998;LoPachin and Lehning, 1994), and axonal transport (Chretien et al, 1981;Miller and Spencer, 1984;Gold et al, 1985;Moretto and Sabri, 1988;Logan and McLean, 1988;Harry et al, 1989;Sabri and Spencer, 1990;Martenson et al, 1995;Sickles et al, 1995Sickles et al, ,1996Stone et al, 2001). However, the minimal effects of AA-treatment, by up to a maximally tolerated dose, on: (i) gene expression related to cholinergic, noradrenergic, dopaminergic, GABAergic, or glutamatergic neurotransmitter systems; (ii) neurotransmitter levels related ...…”
Section: Mode Of Action Of Neurotoxicitymentioning
confidence: 99%